2012
DOI: 10.1210/en.2011-1490
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Chemokine-Like Receptor-1 (CMKLR1) Gene Is Associated with Reduced Adiposity and Glucose Intolerance

Abstract: Adipose tissue secretes a variety of bioactive signaling molecules, termed adipokines, which regulate numerous biological functions including appetite, energy balance, glucose homeostasis, and inflammation. Chemerin is a novel adipokine that regulates adipocyte differentiation and metabolism by binding to and activating the G protein-coupled receptor, chemokine like receptor-1 (CMKLR1). In the present study, we investigated the impact of CMKLR1 deficiency on adipose development, glucose homeostasis, and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(155 citation statements)
references
References 42 publications
9
144
1
1
Order By: Relevance
“…This hypothesis is supported by the suggestion that the activity of the chemerin-CMKLR1 system may depend on the nature of stimuli in the local microenvironment (47). Accordingly, a recent study has reported decreased serum IL6 levels and reduced hepatic inflammatory cell invasion in Cmklr1 K/K mice (22). Complementarily, we found a significant association between the hepatic mRNA levels of IL6 and those of CMKLR1 in our NAFLD subjects, and accordingly when exposing the PHHs to IL6, a significant upregulation of CMKLR1 mRNA expression was observed.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This hypothesis is supported by the suggestion that the activity of the chemerin-CMKLR1 system may depend on the nature of stimuli in the local microenvironment (47). Accordingly, a recent study has reported decreased serum IL6 levels and reduced hepatic inflammatory cell invasion in Cmklr1 K/K mice (22). Complementarily, we found a significant association between the hepatic mRNA levels of IL6 and those of CMKLR1 in our NAFLD subjects, and accordingly when exposing the PHHs to IL6, a significant upregulation of CMKLR1 mRNA expression was observed.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, hepatic CMKLR1 protein expression is reduced in the liver of patients suffering from hepatic steatosis and is upregulated by adiponectin (21), suggesting a protective role of the receptor under conditions of hepatic steatosis. On the other hand, a recent report has indicated decreased serum IL6 levels and reduced hepatic inflammatory cell invasion in Cmklr1 K/K mice (22). Thus, the chemerin-CMKLR1 system seems to be involved in tissue inflammation, which also represents a hallmark of NASH (1,23), but whether the chemerin-CMKLR1 system exerts pro-or anti-inflammatory effects is currently under discussion (19,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that increased chemerin levels represent a compensatory mechanism in metabolic diseases. It has also been shown in mice that a disruption of the CMKLR1 gene is associated with reduced adiposity, but the mice were glucose-intolerant and had a decreased glucose-stimulated insulin secretion [140]. Unfortunately, except for the CMKLR1 intron variant rs1878022 A/G, which was found in a GWAS for the survival rate of patients with nonsmall cell lung cancer [141], no other "common" CMKLR1 genetic variant has been investigated.…”
Section: Chemerin Chemokine-like Receptor 1 (Cmklr1)mentioning
confidence: 99%
“…Une pré-prochémérine est synthé-tisée, sécrétée ensuite sous la forme d'un précurseur inactif, la prochémérine (Figure 1). Celle-ci est activée par clivage de sa partie carboxy-terminale par diffé-rentes enzymes (cathepsine G, plasmine, élastase, ainsi la souris, une invalidation du gène Cmklr1 entraîne une diminution de l'adiposité et une augmentation de l'intolérance au glucose [27] bien que Rouger et al aient observé une augmentation de l'adiposité chez des souris Cmklr1 -/- [28]. L'invalidation de Gpr1, codant le second récepteur de la chémérine, entraîne aussi une intolérance au glucose, mais uniquement au cours d'un régime enrichi en lipides [29].…”
Section: Structure Et Expressionunclassified